Modeling the Temperature Field of the Microwave Heating Asphalt Mixture with the Utilization of a Mathematical Model - Yifei Zhang; Qingxian Wang; Bofu Guo (Applied Bionics and Biomechanics)
Microwave heating asphalt mixture is an auspicious method since it requires a minimum level of outside intervention. It has been a recent method with some certain advantages over conventional ones. To obtain the temperature field of microwave heating asphalt mixture utilizing an oblique horn antenna, the aperture field of the oblique horn antenna was deduced based on the Maxwell equations. The three-dimensional mathematical model of a microwave heating asphalt mixture was established by introducing a position relation of the horn caliber called an oblique horn antenna, and the calculation results were simplified and verified by experiments. The results showed that the calculated values of the mathematical model tally with the experimental outcomes. The model is found to be accurate and reliable.